Virtual and augmented reality in human resource management and development: A systematic literature review - Meirinhos, Viviana (2021)
The growing interest in virtual and augmented reality applied to business leads companies to explore possible applications in several management areas. The application of virtual and augmented reality to human resources management and development is also underway. Despite this growing trend, there is a lack of scientifically grounded information on what is being done, how, and the results. This research aims to fill this gap by mapping the scientific knowledge regarding virtual and augmented reality in human resources management and development. To accomplish this goal, we undertook a systematic literature review following the six main steps of the research protocol: 1) formulation of the research question; 2) definition of objectives for the systematic review; 3) description of inclusion criteria; 4) research strategy; 5) selection procedure; 6) procedure for data extraction and categorization. The findings were analyzed based on two main groups of categories. The first group reports categories related to the document description; the second group is focused on the potential use and impact of virtual and augmented reality in human resources management and development processes. The results show that virtual and augmented reality in human resources management and development is still in a very early stage, requiring more in-depth research. The results so far are promising, namely in terms of the impact that this technology can produce in some human resources management and development processes. Future paths of research are also pointed out.